Will the Real Coeliac Disease Please Stand Up? Coeliac Disease Prevalence in the German LIFE Child Study. Issue 4 (October 2018) - Händel, Norman; Mothes, Thomas; Petroff, David; Baber, Ronny; Jurkutat, Anne; Flemming, Gunter; Kiess, Wieland; Hiemisch, Andreas; Körner, Antje; Schlumberger, Wolfgang; Thiery, Joachim; Wolf, Johannes
ABSTRACT: Objectives: Assessing the seroprevalence and the prevalence of definite coeliac disease (CD) in the German LIFE Child Health study cohort including immunoglobulin A (IgA) antibodies against tissue transglutaminase (IgA-TTG) in addition to IgG antibodies against deamidated gliadin peptides (IgG-DGP) and human leukocyte antigen (HLA)-DQ2/8 genotyping. Methods: Samples from children and adolescents were first screened for IgA-TTG and IgG-DGP. If IgA-TTG was above 0.5 times the upper limit of normal and/or IgG-DGP was positive, IgA antibodies against endomysium (IgA-EmA) were measured, and HLA was genotyped. In patients with only IgG-DGP positivity, total IgA was assayed. Subjects with suspicious results were followed up serologically and, in case of repeatedly positive antibody results, invited for a personal interview. Further diagnostic data were obtained independent from our study. Results: We screened 2363 children's blood samples collected from 2011 to 2015. The seroprevalence, that is, IgA-TTG and/or IgA-EmA positivity or IgG-DGP positivity with IgA <0.05 g/L, was 1.57% (95% confidence interval [CI95% ] 1.14–2.15). The prevalence of suspected CD, that is, seroprevalence and compatible HLA genotype with hitherto unknown mucosal damage, was 1.35% (CI95% 0.96–1.91). Definite CD, that is, seropositivity accompanied by positive intestinal biopsy or IgA-TTG ≥ 10 × upper limit of normal, was found in 0.42% (CI95% 0.22–0.80). Seven children claimed to have CD. The HLA haplotype, however, matched in only 4 of them resulting in an overall CD prevalence of at least 0.59% (CI95% 0.34–1.02). Thirteen unclear cases remained; therefore, the prevalence may even be higher. Conclusions: The prevalence of definite CD in a population-representative German cohort is higher than previously described. HLA-DQ typing is helpful to identify false-positive IgA-TTG patients negative for IgA-EmA and/or IgG-DGP under screening conditions and unmasks possible misdiagnoses of CD. Abstract : Supplemental Digital Content is available in the text